MANAGEMENT OF MADRASAH PRINCIPALS IN IMPROVING THE QUALITY OF EDUCATION AT MAN 1 SUNGAI PENUH CITY IN JAMBI PROVINCE - Jon Kasmadi; Risnita; Fadlilah (As-Sulthan Journal of Education, 2026)
This study examines the management of madrasah principals in improving the quality of education at State Madrasah Aliyah (MAN) 1 Sungai Penuh City, Jambi Province. The research focuses on leadership practices, strategic management, and academic supervision implemented by the principal to enhance institutional performance and teacher professionalism. A qualitative research approach with a descriptive-analytical design was employed. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, and administrative staff. The findings indicate that effective principal management, characterized by visionary leadership, participatory decision-making, and value-based practices, significantly contributes to improving educational quality. Academic supervision plays an essential role in strengthening teacher competencies and instructional effectiveness, while collaborative organizational culture supports continuous improvement. The integration of Islamic values within management practices fosters a holistic educational environment that balances academic achievement and character development. Overall, the study concludes that strong and strategic principal management is a key factor in achieving sustainable quality improvement in madrasah education.